Efektivitas Program Pelayanan Langsung Jadi Administrasi Kependudukan di Desa Tegal Harum, Kecamatan Denpasar Barat - Purdana, I Made; Pandawani , Ni Putu; Sumantra , I Ketut; Sudipa , I Nyoman (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
This study aims to analyze the effectiveness of the Direct Administration Service Program (Pelangi Adminduk) in Tegal Harum Village, West Denpasar District. This study uses a quantitative method, with a population of all households in Tegal Harum Village totaling 3,325 households. A simple random sampling technique was used, resulting in 357 households as the sample. Data were analyzed using research instrumentation tests and descriptive/efficiency. The research results indicate that: (1) The Pelangi Adminduk program in Tegal Harum Village is already effective, as demonstrated by organizational factors and high service recipient satisfaction; (2) The constraints affecting the effectiveness of the Pelangi Adminduk program include existing regulations and employee awareness; (3) Solutions to address these constraints involve (a) improving existing regulations to make them easier to understand and apply, and (b) enhancing employee awareness through intensive socialization.